Preparation of zinc oxide nanoparticles using Citrus sinensis fruit peel aqueous extract and its antimicrobial study - Lamichhane, Yinit Raj; Parajuli, Kshama; Pradhanang, Situ Shrestha (Scientific World, 2024)
The remarkable properties of nanoparticles within the 1 to 100 nm size range have garnered significant attention due to their unique characteristics arising from their small size and high surface-to-volume ratio. In this research, zinc oxide nanoparticles (ZnO NPs) were synthesized using an eco-friendly approach, employing orange fruit peel aqueous extract as a stabilizer as well as biological reducing agent and zinc nitrate hexahydrate as a zinc precursor. This method not only reduces the need for copious amounts of chemicals but also eliminates the use of hazardous substances in the fabrication process, augmenting the antibacterial attributes of the nanoparticles. As synthesized material underwent characterization through X-ray diffraction (XRD) analysis where the prepared material was single phase crystalline ZnO NPs and particle size was measured to be 31.2 nm using Debye-Scherrer’s equation. Energy-dispersive X-ray spectroscopy (EDX) revealed that the sample primarily consisted of 98% zinc with minor impurities such as calcium and potassium in it. Fourier-Transform Infrared (FTIR) analysis exhibited a distinct absorption peak at approximately 550 cm⁻¹, confirming the synthesis of ZnO NPs. The antimicrobial potential of the synthesized ZnO NPs was evaluated against two bacterial strains, Staphylococcus aureus and Escherichia coli, through the Kirby Bauer method on media conducive to bacterial growth. The prepared nanoparticles exhibited bactericidal activity, effectively inhibiting bacterial growth, and generating discernible zones of inhibition.